Crew working on wooden trestle bridge connecting Tunnel Mountain with the south portal of the tunnel during the construction of the White Pass & Yukon Railroad, Alaska, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Bridge at tunnel White Pass and Yukon Route" Original image in Hegg Album 2, page 26.